ВПЛИВ ЕЛЕКТРИЧНИХ ПАРАМЕТРІВ ВИСОКОВОЛЬТНИХ ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК СИНТЕЗУ НАНОВУГЛЕЦЮ НА ЇХНЮ ПРОДУКТИВНІСТЬ І ПИТОМІ ЕНЕРГОВИТРАТИ - Вінниченко, Д.В. (Інститут електродинаміки НАН України, Київ, 2016)
The influence of electrical parameters of high-voltage electric-discharge systems (EDS) for synthesis of nanocarbon on their performance and specific power inputs was experimentally studied. The regularities of influence of electrical and technological characteristics of EDS on synthesis efficiency of nanocarbon materials (NCM) in gaseous carbonic mediums at limited power inputs are determined. References 12, figures 2.